Scorpion vs. tarantula [book with audioplayer] - Adamson, Thomas K., 1970- (Animal battles (Bellwether Media), 2021)
Scorpions and tarantulas may be small. But these two animals know how to fight! In this high-interest title, reluctant readers will learn about how these two creatures get ready to battle. Visual features offer stats and comparisons to highlight traits of each animal. A final fight scene applies the content of the book in an action-packed finale!